Poldrugo stoletje elektromagnetnih valov - Strnad, Janez (Obzornik za matematiko in fiziko, 2014)
The awarenes that light is an elecromagnetic phenomen matured for some lenght of time. The decisive step was taken by James Clerk Maxwell in 1864. A hundred and fifty years ago for the first time the wave equation was derived from equations of the electric and magnetic fields. We are interested in the main twists of this derivation. Maxwell's earlier work and later development are described as well. Nowadays the contributions of others are often overlooked.
Keywords: zgodovina fizike; elektromagnetno valovanje; svetloba; elektromagnetno polje; Maxwellove enačbe